2021
DOI: 10.36408/mhjcm.v8i2.578
|View full text |Cite
|
Sign up to set email alerts
|

Pola Pemberian Antibiotik Di Era Pandemi Covid-19 (Studi Kasus Di Rumah Sakit Nasional Diponegoro)

Abstract: Latar Belakang: Penggunaan antibiotik yang tidak tepat dapat meningkatkan kejadian resistensi antibiotik yang pada akhirnya meningkatkan morbiditas, mortalitas, dan biaya kesehatan. WHO telah merekomendasikan untuk dilakukan kajian rasionalitas penggunaan antibiotik dalam rangka mengatasi masalah resistensi antibiotik. Tujuan: Menganalisis kualitas dan kuantitas penggunaan antibiotik di instalasi rawat inap Rumah Sakit Nasional Diponegoro (RSND). Metode: Penilaian kualitas dan kuantitas penggunaan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…Similar findings were also reported in Dr. R. Koesma Tuban General Hospital, Indonesia, levofloxacin with 83.10 DDD/patient-days [ 16 ]. On the contrary, azithromycin had the highest DDD/100-patient days at Diponegoro National Hospital, Indonesia, while levofloxacin placed second in number [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were also reported in Dr. R. Koesma Tuban General Hospital, Indonesia, levofloxacin with 83.10 DDD/patient-days [ 16 ]. On the contrary, azithromycin had the highest DDD/100-patient days at Diponegoro National Hospital, Indonesia, while levofloxacin placed second in number [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar azithromycin DDD calculation of 44.54 DDD/100-patient days was reported at Prof. Dr. R. D. Kandou General Hospital (tertiary hospital), Indonesia [ 19 ]. Diponegoro National Hospital revealed a higher number of 73.73 DDD/100-patient days among COVID-19 patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study is similar to a study that analyzed the antibiotics utilization with the ATC DDD/ 100 bed days method in the early COVID-19 pandemic where there was the use of beta-lactam antibiotics (ceftriaxone, carbapenems, cephalosporins/betalactamase inhibitors) and azithromycin in a hospital (Gay et al, 2012). Another study stated that the most antibiotics given to COVID-19 patients were azithromycin, levofloxacin, and ceftriaxone, with the value of DDD/bed days respectively 48.12; 44.01; and 21.13 DDD/ 100 bed days (Putra et al, 2021). Sputum cultures of COVID-19 patients were carried out on research samples and observed bacteria growing to determine the possibility of bacterial co-infection in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian yang dilakukan di instalasi rawat inap Rumah Sakit Nasional Diponegoro (RSND) terhadap 141 peresepan antibiotik memperlihatkan bahwa antibiotik yang paling banyak digunakan pada pasien Covid-19 adalah azitromisin, levofloksasin, dan ceftriakson dengan nilai DDD/100 pasienhari masing-masing 48,12; 44,01; dan 21,13. Berdasarkan kriteria gyssens, terdapat 51.1% antibiotik digunakan dengan tidak rasional dan 13.5% tidak ada indikasi penggunaan antibiotik (Putra et al, 2021).…”
Section: Pendahuluanunclassified
“…Meskipun insiden rendah (8%) dari koinfeksi yang dilaporkan diantara pasien dengan Covid-19, 72% pasien menerima terapi antibiotik (Rawson et al, 2020) Antibiotik yang paling banyak diresepkan adalah levofloxacin i.v dengan persentase 35,59% dan antibiotik kedua terbanyak adalah ceftriakson i.v sebesar 30,35%. Levofloksasin dan ceftriakson merupakan antibiotik yang paling sering diresepkan pada pasien Covid-19 (Putra et al, 2021;Khan et al, 2022;Cong et al, 2022). Kedua antibiotik tersebut berasal dari kategori Watch (kategori WHO AWaRe).…”
Section: Hasilunclassified